DEVELOPMENT OF ANDROID-BASED METAVERSE MEDIA TO IMPROVE NUMERATION LITERACY OF CLASS V STUDENTS IN PRIMARY SCHOOLS - Anwar, Salma Rosyida; Nugroho, Wahyu; Pratiwi, Diyanti Jati (PROGRES PENDIDIKAN, 2024)
The research is motivated by the problem of mathematics learning in class V of elementary schools. It is known that students have difficulty collecting data in story form, so students' numeracy literacy is considered low. Research to determine mathematics learning problems related to numeracy literacy in grade V elementary schools. The research uses the Research and Development (RnD) method and the Lee and Owens model. The data collection techniques used were interviews, observation, media validation, materials, language, practitioners, student and teacher responses, numeracy literacy questionnaires, and test questions. The effectiveness test (N-Gain) obtained a mean of 65.4 %. So, the media is considered effective in use, so it is concluded that Android-based metaverse media can increase the numeracy literacy of fifth grade elementary school students.